Putting guidelines into practice: a tailored multi‐modal approach to improve post‐operative assessments. Issue 1 (26th October 2011) - Ford, John A.; MacKay, Craig; Peach, Chris; Davies, Paul; Loudon, Malcolm
Abstract Background The Scottish Intercollegiate Guideline Network (SIGN) published Postoperative Management in Adults in 2004, advocating post‐operative assessments to optimize post‐operative care. Our aim was to improve post‐operative assessments in a surgical high‐dependency unit (HDU). Methods A prospective audit of post‐operative admissions to surgical HDU over two 4‐week periods was performed. Medical and nursing documentations were reviewed. A tailored multi‐modal approach targeting specific barriers to change was used to implement changes; education of staff, introduction of designated HDU bleeps and a post‐operative assessment pro forma. Re‐audit was performed after 6 months. Main findings The first cycle included 72 patients and the second included 62 patients. Time to assessment improved after changes. Forty‐six (74%) patients compared with 27 (37%) patients before were assessed within 4 hours. The number of individual reviews increased and number of reviews due to nursing concerns decreased. Thirty‐eight (61%) patients compared with 15 (21%) patients before were assessed through an individual review and one (2%) patient compared with 23 (32%) patients due to nursing concerns. Documentation improved. Documentation of relevant past medical history, medications, allergies, complications and post‐operative instructions improved from 2 (3%), 1 (1%), 0, 8 (11%) and 26 (36%), to 18 (29%), 28 (45%), 20 (32%), 18 (29%) and 55 (89%), respectively. Difference between first and second cycles was highly significant throughout (P < 0.001). Conclusion Clinical practice was improved by a tailored multi‐modal approach. Educating staff, improving communication and documentation, and re‐audit has shown significant improvement. However, further improvements are required to reach best practice.